The Advantages of Long-Term Investing in Open Investment Funds versus Bank Deposits in Emerging Economies - Besfort Imeri (My University, 2024)
Purpose The capital market, in every country, as well as in the Republic of North Macedonia, has an impact on economic growth and development. Citizens are the main pillar of saving and investing in all fields of economy and finance. Open investment funds in our country, although young, act as direct intermediaries and participants in the capital market (Arsova, 2021). However taking into account that the participation of citizens' investment in open investment funds is relatively low, compared with the more developed countries of Western Europe (Usmanovich, 2018), they are also low compared to investing in bank deposits (Cvetkoski, 2014). Whether our profits differ very much from our choice of investment between open investment funds and banking deposit, and whether should we consider it before investing in long-term investment (Halland et al., 2016). Design/methodology/approach Data were collected from the financial market in North Macedonia, especially from the Central Bank annual reports from the last 10 years (NBRM, 2023). The method of regression analysis is used to determine whether and how much investment from our choice affects those returns between two options of investments in bank deposit or open investment funds. Also, through the scatter diagrams and regression lines we are going to determine if the relation is directly positive or inverse, with the increase in spending on investment in the bank and the investment fund, in cases with increasing the investment deadline. Also, the coefficients of determination will be additionally calculated (Ristevski and Tevdoski, 2016). Findings Although we know that by nature these 2 parameters (investment and returns) are in positive proportion, it has been scientifically analyzed that in long-term there is a direct-positive functional straight-line relationship between these 2 parameters, but also through the scatter diagram and the regression line, our study in this paper showed that given the amount of investment in a bank and an investment fund, the difference in yield is large and grows with increasing investment and the term. Because the final result of the equation seems to be directly positive, additionally we have calculated the coefficient of determination, to finally confirm the significant regression relationship. Practical implementation – This study shows that in emerging economies like North Macedonia, it is very important to analyze and make it known to different investors that there are other opportunities for investment, respectively redirecting their free funds to other investment channels, such as Investment Funds, which bring significantly higher returns, in comparison with bank deposits Originality/value The originality of my paper lies in the direct analysis and examination of data reports given annually by the National Bank of North Macedonia for the past 10 years.
Keywords: Capital Market; Investment Fund; Banking Sector; Investment; Yield; Straight Line Regression; Financial Market